SOFTWARE APPLICATION FOR EMBODIED ENERGY BUILDING CALCULATION: A REVIEW - Anjar Primasetra; Dewi Larasati; Surjamanto Wonohardjo; Iwan Sudradjat (DIMENSI (Journal of Architecture and Built Environment), 2022)
There are two types of building energy consumption, namely embodied energy and building operational energy. Studies on operational energy have been widely discussed, while studies on building embodied energy are still quite rare to be studied, especially in Indonesia. In fact, the calculation of embodied energy, especially on embodied energy material, is important in the design phase of the building because it can be used as the basis for various determinations of building energy values ​​and carbon emissions generated by buildings due to construction activities. By using the right tools in the embodied energy calculation, the building planner can determine the right embodied energy value so that it can support the building energy mitigation. This paper aims to explain the use of embodied energy building calculation software that have been developed with the aim of providing an overview and supporting research development of embodied energy building in Indonesia.